CARBON EMISSIONS DISCLOSURE IN ASIA-PACIFIC: THE ROLE OF CARBON AND FINANCIAL PERFORMANCE IN HIGH-IMPACT SECTORS - Azzahra, Aisyah; Hamzah, Ruth Samantha (Universitas Bunda Mulia, 2025)
Background: Carbon emissions disclosure has gained increasing attention in the corporate world due to growing concerns over climate change and sustainability. Companies are expected to be more transparent in reporting their environmental impacts, particularly in carbon-intensive industriesObjective: This study aims to analyze the influence of carbon performance and financial performance on carbon emissions disclosure among industrial companies in the Asia-Pacific, focusing on the energy, chemical, and utilities sectors.Research Methods: A quantitative approach was employed using panel data regression analysis. The study analyzed a sample of 108 companies across three industrial sectors from 2019 to 2023. Data were collected from the LSEG Analytics Workspace via the Refinitiv financial database.Research Results: The findings reveal that Carbon Performance (CP) has a positive and significant effect on Carbon Emissions Disclosure (CED). Financial Performance (FP) also shows a positive relationship with CED, although with lower statistical significance. This indicates that companies with higher carbon efficiency are more likely to disclose carbon emissions transparently.Originality/Novelty of Research: This study contributes to the existing literature by offering recent empirical evidence from Asia-Pacific industrial sectors and highlighting the comparative roles of environmental and financial factors in influencing carbon disclosure practices.